(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective The levels of increased reactive oxygen species (ROS) in presence of liver disorder might enhance lipid membrane peroxidation as well as manufacturing of inflammatory molecules, concluding in cellular damage and death. Cadmium is known to promote body’s ROS production leading to liver damage. L-Carnitine may lower oxidative stress, decrease inflammation, and increase antioxidant enzymes. ROS alters protein transcription and affects the mTOR network signaling. This study, therefore, investigated expression levels of important members of this pathway, mTOR, Akt1, and Akt2, in liver tissues obtained from rats treated with cadmium and L-Carnitine. Materials and methods Four distinct experimental groups were formed comprising of a total of 24 female rats that were administrated with the subsequent treatments orally for a period of 28 days. Cadmium was given to the first group at a dose of 2 mg/kg twice a week. The second group was provided with the same dose of cadmium as the previous group in conjunction with L-Carnitine 75 mg/kg daily. The third group was presented with L-Carnitine 75 mg/ kg every day. Finally, the fourth group constituted the control group. Rats were euthanised to obtain liver samples and RNA was isolated to provide the template for cDNA synthesis. Results and Discussion The results displayed that there was no statistical significance in the difference between the expression levels of mTOR, Akt1, and Akt2 among the control and study groups, respectively. This study showed that, administration of cadmium and L-Carnitine does not influence the activity levels of key mTOR pathway genes. Further studies will include expression analysis of other organs such as kidneys to investigate the interactions among cadmium and L-carnitine administration. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 614-620